Examination of the reduction in natural frequency of laterally loaded piles due to strain-dependence of soil shear modulus. (15th August 2022) - Prendergast, L.J.; Igoe, D.
Abstract: Society's transition to low-carbon energy sources has resulted in significant expansion in offshore wind technology. Most offshore wind turbines (OWTs) are founded on large-diameter steel tubular piles driven into the seabed, termed monopiles. OWTs are subjected to large numbers of dynamic and cyclic environmental loads during their lifetime. To avoid fatigue or resonance issues, accurate characterisation of soil-structure interaction under operating and extreme conditions is paramount. There is a need to further improve understanding of the dynamic lateral response of piles after large lateral load cycling (storm events). This paper presents the results of lateral load field tests on piles with two different slenderness ratios, where the natural frequency was measured after a series of applied lateral load-unload events. 1D numerical models of the piles were developed and several operating parameters were varied to identify the parameters of importance in the nonlinear soil-pile interaction. Approaches to estimate the operating soil shear modulus both in-situ and post load-unload were trialled, and five subgrade reaction models were used to couple soil and pile properties, to ascertain the performance at predicting the measured frequencies from the experiments. Results suggest that predicted frequencies are highly sensitive to choice of model and degradation method used. Highlights: Paper investigates the natural frequency of laterally-loaded piles. A range of methods for in-situ shear modulus estimation are trialled. Degradation in shear modulus with strain characterised using hyperbolic formula. Soil-pile interaction coupling using subgrade reaction methods are employed.